A Bridge Too Far – Revisited: Reframing Bruer’s Neuroeducation Argument for Modern Science of Learning Practitioners - Horvath, Jared C.; Donoghue, Gregory M. (Frontiers in Psychology, 2016)
In Education and the Brain: A Bridge Too Far, John Bruer argues that, although current neuroscientific findings must filter through cognitive psychology in order to be applicable to the classroom, with increased knowledge the neuroscience/education bridge can someday be built. Here, we suggest that translation cannot be understood as a single process: rather, we demonstrate that at least four different ‘bridges’ can conceivably be built between these two fields. Following this, we demonstrate that, far from being a matter of information lack, a prescriptive neuroscience/education bridge (the one most relevant to Bruer’s argument) is a practical and philosophical impossibility due to incommensurability between non-adjacent compositional levels-of-organization: a limitation inherent in all sciences. After defining this concept in the context of biology, we apply this concept to the learning sciences and demonstrate why all brain research must be behaviorally translated before prescriptive educational applicability can be elucidated. We conclude by exploring examples of how explicating different forms of translation and adopting a levels-of-organization framework can be used to contextualize and beneficially guide research and practice across all learning sciences.